Auditory Memory Decay as Reflected by a New Mismatch Negativity Score Is Associated with Episodic Memory in Older Adults at Risk of Dementia - Laptinskaya, Daria; Thurm, Franka; Küster, Olivia C.; Fissler, Patrick; Schlee, Winfried; Kolassa, Stephan; von Arnim, Christine A. F.; Kolassa, Iris-Tatjana (Frontiers in Aging Neuroscience, 2018)
The mismatch negativity (MMN) is an event-related potential peaking about 100-250 ms after a deviant onset in a sequence of identical (standard) tones. Depending on the interstimulus interval (ISI) between standard and deviant tones, the MMN is suitable to investigate pre-attentiveautomatic auditory discrimination ability (short ISIs, ≤ 2 s) as well as pre-attentive auditory memory trace (long ISIs, > 2 s). However, current results regarding the MMN as a biomarker for mild cognitive impairment and dementia are mixed, especially after short ISIs: while the majority of studies report positive associations between MMN and cognition, others fail to find such relationships. To elucidate these so far inconsistent results, we investigated the validity of the MMN as a biomarker for cognitive impairment exploring the associations between different MMN indices and cognitive performance, especially episodic memory as a core symptom of Alzheimer’s dementia, at baseline and at a 5-year follow-up. We assessed the amplitude of the MMN for short ISIs (stimulus onset asynchrony, SOA = 0.05 s) and for long ISIs (3 s) in a neuropsychologically well-characterized cohort of older adults at risk of dementia (subjective memory impairment, amnestic and non-amnestic mild cognitive impairment; n = 57). Furthermore, we created a novel difference score (ΔMMN), defined as the difference between MMNs to short and to long ISIs, as a measure to assess the decay of the auditory memory trace. ΔMMN and MMN amplitude after long ISIs, but not the MMN amplitude after short ISIs, was positively associated with episodic memory at baseline (β = 0.38, p = 0.003; β = -0.27, p = 0.47, respectively). ΔMMN, but not the MMN for long ISIs, was also positively associated with episodic memory performance at the 5-year follow-up (β = 0.57, p = 0.013). The results suggest that the MMN after long ISIs might be suitable as an indicator for the decline in episodic memory and indicate ΔMMN as a potential biomarker for memory impairment in older adults at risk of dementia.